Development and testing of an advanced practice clinical advancement program within an academic medical center. Issue 9 (7th September 2021) - Kapu, April N.; Card, Elizabeth; Jackson, Heather; Kinch, Jill; Lupear, Buffy Krauser; LeBar, Kiersten; Moore, Deonna; Terrell, Michelle; Dubree, Marilyn
ABSTRACT: Background: Faculty advanced practice registered nurses (APRNs) and physician assistants (PAs) employed by Vanderbilt University Medical Center (VUMC) have historically participated in rank promotion tracks for recognition of professional accomplishments in education, practice, and research. However, there has not been a clinical advancement program for nonfaculty practitioners. Satisfaction, engagement, and health surveys indicated VUMC APRNs and PAs were seeking opportunities for professional growth and development. Many health care organizations have incorporated clinical advancement programs as key recruitment and retention strategies. With a growing number of nonfaculty APRNs and PAs, VUMC began to explore the development, implementation, and evaluation of a clinical advancement program. Purpose: A VUMC Clinical Advancement Task Force was created to explore, develop, implement, and evaluate an advanced practice clinical advancement pilot. Methods: Two teams were selected to participate in a 6-month pilot. Presurveys and postsurveys were conducted, and postpilot focus groups were held with participating practitioners. A 9-square tool was developed as a rubric for evaluating the practitioner's progress. Applications, leader assessments, and recommendations were housed in a secure database for a selected advancement committee to evaluate. Results: Of 23 participants, 47% indicated satisfaction with professional development opportunities, when compared with 84% postpilot. Postpilot focus groups further improved the tool and the process for the program. Implications for practice: Opportunities for advancement/professional development positively influence APRN and PA perceptions of job satisfaction. This program could be tested with other APRN and PA teams for impact on job satisfaction, engagement, and retention.